THE EFFECTIVENESS OF COLLABORATIVE STRATEGIC READING (CSR) TOWARDS THE READING COMPREHENSION OF THE FIRST GRADE STUDENTS OF SMAN 14 PEKANBARU - Septiani, Riri; ', Marzuki; ', Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This pre-experimental research aimed to find out the significant effect of Collaborative Strategic Reading (CSR) towards the reading comprehension of the first grade students of SMAN 14 Pekanbaru. This study was one group pre-test and post-test design. The population of this study was grade X students of SMAN 14 Pekanbaru which consisted of 7 classes with the total of 259 students. The sample of this study was X.4 class with 37 students. The instrument of the research was a reading test with multiple choice type. The test consisted of six texts where each text contained eight questions with five options (A,B,C,D and E). The writer conducted a try out before the treatment was held. The level difficulty formula by Heaton was used in this study to obtain the reliability and validity of the test. Furthermore, the t-test formula was used in order to analyze the data. The T-Test displayed that the results determined by the probability of sig. > 0.05, probability=0.000, that showed a strong correlation between Collaborative Strategic Reading (CSR) and students’ reading comprehension. t-obs result also showed that the students’ mean score of the post-test (67.04) was higher than the pre-test ( 54.59). Besides, the results of the analysis showed that the t-test was higher than the t-table (12.45>2.028) at the level sig. of 0.05 with the degree of freedom (df) n-1=36. It means that the alternative hypothesis was accepted and null hypothesis was rejected. Based on the data calculation, the results showed the significant effects of Collaborative Strategic Reading (CSR) towards the reading comprehension of the first grade students.Keywords: Collaborative Strategic Reading (CSR), reading comprehension